Effectiveness of the production and marketing analysis service (PMAS) the case of vegetable farmers in Dalaguete, Cebu - Sinoy, Ronald H. (University of the Philippines in the Visayas, 2005)
The study was conducted primarily to determine the effectiveness of PMAS to vegetable farmers. Specifically, it aims to determine the income and productivity level of farmers and obtain their perception about its adoption as well as the problems encountered by farmers in the process of adopting the PMAS. A total of 20 respondents in selected barangays of Dalaguete, Cebu were interviewed. Results were presented through simple descriptive statistics. Results showed that the average age of the respondents is 46 years old, mostly males (85%) and married (95%) and having a family size of six members. The educational attainments of the respondents is quite high with 30% able to reach high school and 15% college level. While majority of them live in concrete houses (55%), the land they cultivated were mostly tenanted (60%). The average farm size of the farmers is about 0.75 of a hectare which somehow limits their production capabilities. Vegetable farming is the primary source of livelihood of all respondents. There were also notable increases in income levels of majority of the respondents after PMAS was introduced. Generally, all the respondents have attended different trainings mostly o crop production (90%), more specifically on vegetable production technology.Eghty percent of them were active members of different farmer's associations. The beneficiaries who adopted the program and uses production planning (65%) claimed that the timing of harvest when the price is highwas their primary benefit. But there were also problems encountered by farmers in the adoption of production planning. Their lack of price control (35%) particularly when there is oversupply of products was their ultimate concern asprices were usually controlled by wholesalers (40%). There was also a slight increase in their production at 3.0-5.0 metric tons bracket. Despite the objective of the program of empowering the farmers to take a greater bargaining power, prices were still controlled bytraders. Lack of coordination and control among themselves and the different farmers associations make them susceptible to price manipulations. But somehow their knowledge on price information lessens the degree of price control of traders. Overall the farmers gave asatisfactory rating for the program with the perception that if properly adopted by majority of the farmers and farmers association, it will really help improved their economic conditions.